TRANSFORMASI DIGITAL MELALUI PTMGRMD : UPAYA MENINGKATKAN KUALITAS HIDUP MASYARAKAT DESA CIPICUNG CIKEDAL PANDEGLANG - Adha, Suhroji; Aliyah, Siti Nur; Ramadhan, Dafa Sauqi; Sasongko, Shevila Ghita; Muanifah, Suciati; Lathifah SD, Fifit; Irmayani, Okta; Kusuma, Jaka Wijaya; Hidayat, Syamsul (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The Independent Higher Education Program Gotong Royong Pembangunan Desa (PTMGRMD) is an initiative that aims to improve the quality of life of village communities through digitalization and multi-stakeholder collaboration. The main focus of this program is Cipicung Village in Banten Province, which faces various challenges in access to information, education, and health. Through the application of the pentahelix model involving universities, local governments, communities, and the private sector, PTMGRMD seeks to empower the community by providing information technology training, as well as developing local superior products. The program also seeks to create an inclusive and participatory environment, where communities are involved in every stage of the development process. Despite challenges such as resistance to change and limitations of infrastructure, the proposed solutions include intensive socialization and basic infrastructure development. Thus, PTMGRMD is expected to have a sustainable positive impact on the people of Cipicung Village and become a model for other villages in Indonesia in utilizing technology to improve welfare.